2021
DOI: 10.3389/fncir.2021.663633
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Septo-Hippocampal Neural Responses in Anesthetized and Behaving Rats by Septal AMPA Receptor Mechanisms

Abstract: This study explored the effects of septal glutamatergic transmission on septal-hippocampal theta activity via intraseptal microinjection of antagonist at AMPA receptors (AMPAR). The current results showed that microinjection of AMPAR antagonist, NBQX (2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo[f]quinoxaline-2,3-dione, 20 μg/μl, 0.5 μl), evoked a decrease in the frequency of theta activity evoked by various means in anesthetized and behaving rat. Theta wave activity was induced on: (a) intraseptal microinjection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…8 A–C ). These results are consistent with increased locomotion/agitation and grooming seen following injection of formalin into the hindpaw ( 77 79 ). We believe that the chemogenetic Y1-IN activation-induced increase in movement is an index of nociception rather than anxiety.…”
Section: Resultssupporting
confidence: 82%
“…8 A–C ). These results are consistent with increased locomotion/agitation and grooming seen following injection of formalin into the hindpaw ( 77 79 ). We believe that the chemogenetic Y1-IN activation-induced increase in movement is an index of nociception rather than anxiety.…”
Section: Resultssupporting
confidence: 82%
“… 25 This might be caused by loss of MS neurons, which disrupts the functional connectivity of the MS–hippocampus pathway. Another study 26 explored the effects of MS glutamatergic transmission on hippocampal θ power via an MS microinjection of antagonist α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionic acid receptors (AMPARs). The results showed that microinjection of an AMPAR antagonist induced a decrease in the frequency of θ power in the anesthetized rat.…”
Section: The Role Of Bf In General Anesthesiamentioning
confidence: 99%